Pengaruh Kelengkapan Produk Dan Promosi Terhadap Keputusan Pembelian Pada Kembar Store Sidomulyo di Lampung Selatan - Baiti, Ana Nur; Saodin, Saodin (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
Purchasing Decisions are several stages carried out by consumers before making a decision to purchase a product, which is influenced by Product Completeness and Promotion. This research aims to determine the influence of product completeness and promotion on purchasing decisions at the Sidomulyo Store Twins in South Lampung. The type of research used in this research is Quantitative Research, with the sampling technique used in this research being Non Probability Sampling with the Accidental Sampling technique. To find the validity test of the instrument using Pearson Product Moment, while the Reliability Test uses Cronbach's Alpha and the Classical Assumption Test. The analytical methods used to answer this research are the Multiple Linear Regression Test, the Coefficient of Determination Test and the Instrument Test t Test and F Test. Based on partial calculation results: Product Completeness influences Purchasing Decisions and Promotion influences Purchasing Decisions at Sidomulyo Store Twins in South Lampung. Based on the results of simultaneous calculations: Product Completeness and Promotion simultaneously influence Purchasing Decisions at Sidomulyo Store Twins in South Lampung.